Cyber Warfare: National Security In Dealing With Changing Method of War - Maskun Maskun; Azhar Risaldy Rum (Universitas Syiah Kuala, 2021)
The purpose of this research is to identify cyber warfare as a model of War, its position in the perspective of international law, and the steps taken by the state in minimizing losses arising from cyber warfare. This research is normative research using conceptual and statute approaches to answer the problems in this research. The analysis used is content analysis. The study results indicate a need for a common understanding of cyber warfare as a new model of war agreed upon by countries in practice. Normative cyber warfare in international law has to be applied universally. The periodic simulations of cyber defense and artificial intelligence are needed in minimizing the losses caused by cyber warfare. The recommendation is to formulate a definition of cyber warfare universally agreed upon and the state's agreement on the meaning of cyber warfare in international law perspectives.